Stability Analysis of Networked Control System Using LMI Approach - Sharma, Richa; Nagaria, Deepak (International Journal of Engineering and Technology, 2018)
Networked control system is a closed loop system in which information or data travel through the communication network. The presence of communication network will increase time delay and information losses. Due to these losses and delay the performance of the system decreases. This paper represents an analysis to find the stability of the networked control system with the varying time hindrances present in the network. In this research, it has been assumed that the delay in time is less than the sampling period. The stability conditions for NCS have been procured with the use of the Lyapunov function approach and has been described in terms of LMI(Linear Matrix Inequality).This examination confirm the adequate state of stability through MATLAB simulation and the numerical case demonstrates the outcome.Â Â